Feedback sensitivity functions analysis of finite‐time stabilizing control system. (25th October 2016) - Zimenko, K.; Polyakov, A.; Efimov, D.; Kremlev, A.
Summary: This paper presents feedback sensitivity functions analysis of implicit Lyapunov function‐based control system in case of finite‐time stabilization problem. The Gang of Four is chosen as a feedback sensitivity tool. The results can be used for parametric tuning of control algorithms in order to guarantee desired closed‐loop sensitivity specifications. The obtained results are supported by numerical examples. Copyright © 2016 John Wiley & Sons, Ltd.